A Tale of Two Species Revisiting the Effect of Registration Reform on Informal Business Owners in Mexico - Bruhn, Miriam (The World Bank, 2012)
Different views have been put forward to explain why most firms in developing countries operate informally. One view argues that informal-business owners are entrepreneurs who do not register their firm because the regulation process is too complex. Another argues that informal-business owners are people trying to make a living while searching for a wage job. This paper contributes to recent literature that argues that both factors are at work. The author uses discriminant analysis to separate informal business owners into two groups: those with personal characteristics similar to wage workers, and those with traits similar to formal-business owners. The paper then examines how the two groups were affected by a business registration reform in Mexico. Informal-business owners from the second group were more likely to register their business after the reform. By contrast, informal-business owners from the first group were less likely to register but more likely to become wage workers after the reform. This is consistent with the finding in Bruhn (2008 and 2011) that the reform led to job creation. It also explains why the earlier papers find that the reform didn?t affect the number of new registrations by all informal business owners